Pengaruh Gaya Mengajar Komando Terhadap Keterampilan Gerak Dasar Gaya Dada pada Siswa SMA Negeri 7 Manado - Willy Alsalira Telap; Lolowang Lolowang; Mangindaan Mangindaan (STIKES Columbia Asia Medan, 2025)
This research aims to determine the effect of applying the command teaching style on the fundamental breaststroke skills of male students at SMA Negeri 7 Manado. Using an experimental method with a randomized control group pre-test and post-test design, data were collected from 30 students divided into experimental and control groups. The experimental group received treatment using the command teaching style, while the control group followed conventional instruction. The results showed a significant increase in breaststroke skill scores in the experimental group compared to the control group, with a mean gain of 4.00 and 0.46 respectively. Statistical analysis using a t-test revealed that the command teaching style significantly improves basic swimming skills. These findings suggest that the command teaching method is effective for developing movement precision and discipline in physical education, particularly for skill-based learning such as swimming techniques.